2006
DOI: 10.1039/b608329n
|View full text |Cite
|
Sign up to set email alerts
|

A novel electrochemical device for the disinfection of fluids by OH radicals

Abstract: This paper describes a novel, composite device, based not on optical excitation but on the transfer of holes from Si to the TiO(2)/air or TiO(2)/water interface, for the disinfection and detoxification of fluid streams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 11 publications
(14 reference statements)
1
18
0
Order By: Relevance
“…Recent research has demonstrated that electrochemistry offers an attractive alternative to the above-mentioned traditional methods for treating wastewaters [16][17][18][19][20][21][22]. Electrochemical coagulation, which is one of these techniques, is the electrochemical production of destabilization agents that brings about charge neutralization for pollutant removal, and it has been used for water or wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated that electrochemistry offers an attractive alternative to the above-mentioned traditional methods for treating wastewaters [16][17][18][19][20][21][22]. Electrochemical coagulation, which is one of these techniques, is the electrochemical production of destabilization agents that brings about charge neutralization for pollutant removal, and it has been used for water or wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%
“…3 Nevertheless, the stability and unusual electrocatalytic properties can be obtained with a composite anode based on a TiO 2 and Si heterojunction [27,28]. P-n semiconductors heterojunctions have been explored previously as photoactive materials for photocatalytic applications [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The term e À2ah in Eq. (24) reflects the extent of lateral interaction, if a > 0 indicates attraction, while a < 0 means repulsion (41). From Table 5, we see that the value of a is À0.525 indicating the attraction.…”
Section: Frumkin Equationmentioning
confidence: 93%
“…Usually magnesium and aluminium plates are used as electrodes in the electrocoagulation followed by the electrosorption process (17)(18)(19). The advantages of electrocoagulation include high particulate removal efficiency, a compact treatment facility, relatively low cost, and the possibility of complete automation (20)(21)(22)(23)(24)(25). This technique does not require supplementary addition of chemicals and reduces the volume of produced sludge.…”
mentioning
confidence: 99%